Study on Effect of Human Metabolic Rate on Skin Temperature in Office Environment - R. A., Bakar; Norfadzilah, Jusoh; Ahmad Rasdan, Ismail; T. Z. S., Ali (2016)
The motivation of this study is to get better understanding about the real thermal sensation of people in office environment who undertake moderate activities. All measurements were conducted in a climate chamber. In total, fifteen subjects were participated in three kinds of activities, their skin temperatures and thermal sensation were measured. Skin temperatures (eleven locations) were measured using thermocouple sensors. The results showed that the temperature is the one of factors which affect metabolic rate. There is a strong linear relationship between these three tasks of metabolic rate with skin temperature. Furthermore, the results indicate that there was a greater increase thermal sensation when the metabolic rate 1.6.